2022
DOI: 10.3389/fnut.2022.815578
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status According to the Short-Form Mini Nutritional Assessment (MNA-SF) and Clinical Characteristics as Predictors of Length of Stay, Mortality, and Readmissions Among Older Inpatients in China: A National Study

Abstract: BackgroundStudies are scarce in China that explore the association of nutritional status, measured using the Short-Form Mini Nutritional Assessment (MNA-SF) and biochemical data, on adverse clinical outcomes among older inpatients. In this study, we aimed to determine the prevalence of malnutrition in tertiary hospitals of China and the associations between malnutrition and adverse clinical outcomes.MethodsThis prospective study involved 5,516 older inpatients (mean age 72.47 ± 5.77 years) hospitalized in tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 63 publications
1
30
1
Order By: Relevance
“…MNA ® -SF is also a nutritional assessment tool speci c for older adults, and its scores have been reported to be associated with prognosis [11,[19][20][21]. The results of this study showed an HR of 2.17 for malnutrition; however, no signi cant association was observed between at risk, malnutrition, and prognosis.…”
Section: Discussioncontrasting
confidence: 57%
“…MNA ® -SF is also a nutritional assessment tool speci c for older adults, and its scores have been reported to be associated with prognosis [11,[19][20][21]. The results of this study showed an HR of 2.17 for malnutrition; however, no signi cant association was observed between at risk, malnutrition, and prognosis.…”
Section: Discussioncontrasting
confidence: 57%
“…Most patients in this study had bone and joint diseases (42.5%), whereas fewer patients with cardiovascular and kidney diseases were prone to developing edema, suggesting that the GNRI strongly contributed to the prognosis, as reported in previous studies. MNA Ⓡ -SF is also a nutritional screening tool specific for older adults, and its scores have been associated with prognosis [11,[21][22][23]. The results of this study showed an HR of 2.17 for malnutrition; however, no significant association was observed between risk, malnutrition, and prognosis.…”
Section: Discussionmentioning
confidence: 50%
“…The Mini-Nutritional Assessment Short Form (MNA-SF) [ 32 ] was used to assess baseline malnutrition risk at admission to the post-acute care unit. Scores < 11 indicate risk of malnutrition [ 49 , 50 ].…”
Section: Methodsmentioning
confidence: 99%